The Effectiveness Of Vaccination Programs in Controlling Infectious Diseases in Low-Income Countries - Dwi Santosa; Maria Yuliana; Budi Prasetyo; Rina Hartati (International Journal of Public Health, 2024)
This study evaluates the effectiveness of vaccination programs in reducing the incidence of infectious diseases in low-income countries. By analyzing immunization coverage data and disease prevalence rates, the research highlights the successes and challenges faced by vaccination initiatives. The findings indicate that comprehensive vaccination campaigns significantly decrease morbidity and mortality rates, emphasizing the need for sustained investment and community engagement to improve public health outcomes.